EKSISTENSI BAHASA IBU DALAM KOMUNIKASI MAHASISWA GAYO DI UIN AR-RANIRY BANDA ACEH - syahdatul fitriani; Fairus; Salman yoga (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the existence of the Gayo language in the communication practices of Gayo students in Banda Aceh, particularly within academic and social settings. As a mother tongue, the Gayo language holds an important function as a marker of cultural identity and a symbol of social cohesion. However, its presence faces challenges in a multiethnic and academic environment. This research employed a descriptive qualitative approach, with data collected through in-depth interviews with Gayo students pursuing their studies in Banda Aceh. Data analysis was conducted by interpreting the informants’ responses and comparing them with sociolinguistic theories, particularly those related to language use and code-switching phenomena. The findings reveal that the Gayo language is still used, especially in informal communication among Gayo students, but its usage is limited and tends to shift toward Indonesian in formal or cross-ethnic contexts. Social environment, academic interaction, and speakers’ attitudes are identified as the main factors driving this language shift. In conclusion, the Gayo language continues to exist among students, yet its use is flexible and highly dependent on the communicative context. Efforts to preserve the Gayo language remain necessary, both through student communities and institutional support, to prevent it from becoming increasingly marginalized.